PARP‐1 Inhibition Increases Oxidative Stress in Ets‐1‐Expressing MDA‐MB‐231 Breast Cancer Cells - Magalie Hervieu; Arnaud J. Legrand; Emilie Floquet; Thierry Idziorek; Corentin Spriet; Didier Monté; Vincent Villeret; Marc Aumercier; Souhaila Choul‐li (Cancer Reports)
ABSTRACT Background The Ets‐1 transcription factor plays a primordial role in regulating the expression of numerous genes implicated in cancer progression. In a previous study, we revealed that poly(ADP‐ribose) polymerase‐1 (PARP‐1) inhibition by PJ‐34 results in Ets‐1 level increase in cells, which is related with cell death of Ets‐1‐expressing cancer cells. Aims The mechanism of the antitumor effect of PARP‐1 inhibition was investigated in the Ets‐1‐expressing MDA‐MB‐231 breast cancer cells. Methods and Results We tested the effects of four PARP inhibitors (PARPi) (PJ‐34, Veliparib, Olaparib, and Rucaparib). We first demonstrated that PARPi reduced cells growth through G2/M cell cycle arrest. Next, we evaluated PARP‐1 inhibition effect on oxidative DNA damage in Ets‐1‐overexpressing and Ets‐1‐non‐expressing breast cancer cells and we showed that PARPi led only Ets‐1‐overexpressing cells to accumulate it, which triggers the DNA damage response as revealed by the increase in the level of a panel of DNA damage‐related proteins. Importantly, we demonstrated that PARPi increased reactive oxygen species (ROS), only in Ets‐1‐overexpressing cells and this is accompanied by upregulation of p47phox expression, a subunit of the NAPDH oxidase (NOX). Conclusion These preliminary findings correlate PARPi‐induced oxidative DNA damage/oxidative stress to Ets‐1 expression in breast cancer cells.